(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study aimed to measure the level of organizational trust with its dimensions (trust in organization, trust in immediate supervisor, trust in coworkers) in Jordanian universities and its impact on job loyalty. A random sample of 364 employee work in Jordanian universities was selected. SPSS was employed to analyze. the result and test the hypotheses The study found that the trends of the sample members were towards the high relative importance of the dimensions of organizational trust in Jordanian universities. The sample members’ attitudes towards the high relative importance of job loyalty in Jordanian universities were also. The results of the statistical analysis showed the existence of a statistically significant role of organizational trust with its dimensions (trust in organization, trust in immediate supervisor, trust in coworkers) in job loyalty in Jordanian universities. The study recommends the decision makers in universities to enhance the organizational trust among their employees to increase their loyalty, through the use of fair and acceptable procedures by supervisors, encouraging cooperative relations and openness to workers’ opinions by opening mutual dialogues in order to communicate information related to the organization to them continuously.